Clinical and Radiological Profile in Non Hypertensive Intracerebral Haemorrhage-A Prospective Observational Study - Siddaganga; Bharat L Konin; Swathi Bhat (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Intracerebral Haemorrhage (ICH) is less frequent than ischaemic stroke, but has higher mortality and morbidity, it being one of the first causes of severe disability. Hypertension is the most common cause of ICH but Non Hypertensive Intracerebral Haemorrhages (NHICH) are not rare. Hence, the importance of recognising these conditions and need for urgent specific therapy which may play a vital role in therapeutic planning and prevention of ICH. Hence this study was performed to study. Aim: To study the clinical and radiological profile in NHICH to identify risk factors, and to determine whether clinical/ neuroradiological parameters would predict the prognosis of ICH. Materials and Methods: The present prospective observational study was conducted in the Department of General Medicine Mahadevappa Rampure Medical College Gulbarga, Karnataka, India, from January 2016 to January 2017. It involved 50 subjects with NHICH. Demographic details, clinical and radiological data was collected in patients presenting with signs and symptoms of stroke and confirmed by Computed Tomography (CT) scan/ Magnetic Resonance Imaging (MRI) brain as ICH, who were non hypertensive and with age more than 18 years. Clinical outcome of the patients were measured based on Glasgow Coma Scale (GCS), site and volume of haemorrhage. Descriptive statistics of the explanatory and outcome variables were calculated by mean, Standard Deviation (SD) and Chi-square test was applied for qualitative variables. Results: In the present study 31 (62%) were males, and 19 (38%) were females. The age of patients ranged from 18-85 years. The most common risk factor associated with intracerebral haemorrhage was alcohol consumption 16 (32.0%), followed by smoking 13 (26%), and anticoagulant intake 13 (26%). Most common clinical presentation were hemiplegia/hemiparesis, speech defect, vomiting, convulsion, pupillary defect and cranial nerve involvement, in decreasing frequency. High ICH score and low GCS were poor prognostic factors for outcome of intracerebral haemorrhage patient in the present study. In hospital mortality rate was 28%. During 30 days follow-up, there was 22.2% mortality among the discharged patient. Conclusion: Although hypertension remains a most common risk factor for intracerebral bleed, other risk factors such as significant alcohol consumption, coagulopathy should also be kept in mind especially in young individual. Non hypertensive haemorrhage usually occurs at sites not typical for hypertensive bleed. All efforts should be directed to establish the aetiological factors for intracerebral bleed, so that appropriate timely therapy can be provided to prevent further morbidity and mortality.